Effectiveness of Interactive Education on Cardiovascular Risk in Increasing Knowledge of Reproductive Age Women for Prevention of Pregnancy Complications - Fiona Paramitha; Alviannur Halim; Tri Putra Rahmad Ramadani; Erick Tanara; Rahmantio Adi; Iman Rachmanto (Jurnal EduHealth, 2025)
Pregnancy complications related to cardiovascular disease are a significant cause of maternal morbidity and mortality in Indonesia, exacerbated by low health literacy among women of reproductive age. Effective education is a key intervention, but the most impactful model still needs to be explored. This study aims to evaluate the effectiveness of a multimedia-based interactive education program in increasing knowledge about cardiovascular risk as a preventive measure for pregnancy complications in women of reproductive age. This study uses a quasi-experimental design with a one-group pretest-posttest approach. A total of 17 women of reproductive age (20-35 years) in Malang, who were members of the Indonesian Midwives Association, participated in this program. The intervention consisted of face-to-face education sessions that combined lectures, discussions, and posters and videos. Participants' knowledge was measured before and after the intervention using a validated questionnaire. Data analysis was performed using descriptive statistics and the Wilcoxon signed-rank test. The results showed a statistically significant increase in participants' knowledge scores after the intervention (Z = -2.810$, p = 0.005). The average knowledge score increased from 94.12 (SD = 11.21) on the pre-test to 95.29 (SD = 11.72) on the post-test. All program outputs, including educational modules, media publications, and activity videos, were successfully completed. The interactive education model proved effective in increasing the knowledge of women of reproductive age about cardiovascular risks in pregnancy.